2022
DOI: 10.3390/hydrology9020026
|View full text |Cite
|
Sign up to set email alerts
|

Application of Numerical and Experimental Modeling to Improve the Efficiency of Parshall Flumes: A Review of the State-of-the-Art

Abstract: One of the primary steps in managing the flow in an open channel is determining its properties. Empirical equations are developed to provide further information regarding the flow in open channels. Obtaining such experimental equations is expensive and time consuming; therefore, alternative solutions have been sought. Over the last century, the Parshall flume, a static measuring device with no moving parts, has played a significant role in measuring the flow in open channels. Many researchers have focused thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Flumes are commonly used to measure flow for various monitoring settings, such as field runoff, stormwater, municipal storm sewers, dam seepage discharge, industrial effluent discharge, watershed monitoring, irrigation canal discharge, ditch and furrow discharge, spring discharge, mine discharge, and stream gauging (Tekade et al, 2016, Heyrani et al, 2022Luxmi et al, 2022;Heiner and Barfuss, 2011;Marr et al, 2010;USBR, 2001;Todeschini et al, 2020;Ribeiro et al, 2021).…”
Section: Field Application Of Flumesmentioning
confidence: 99%
See 2 more Smart Citations
“…Flumes are commonly used to measure flow for various monitoring settings, such as field runoff, stormwater, municipal storm sewers, dam seepage discharge, industrial effluent discharge, watershed monitoring, irrigation canal discharge, ditch and furrow discharge, spring discharge, mine discharge, and stream gauging (Tekade et al, 2016, Heyrani et al, 2022Luxmi et al, 2022;Heiner and Barfuss, 2011;Marr et al, 2010;USBR, 2001;Todeschini et al, 2020;Ribeiro et al, 2021).…”
Section: Field Application Of Flumesmentioning
confidence: 99%
“…The Parshall flume was originally developed in 1926. After further improvements, in 1930, the flume was named after Ralph L. Parshall, the engineer who designed it (Heyrani et al, 2022). The flume consists of a converging section, a throat section, and diverging section.…”
Section: Parshall Flumementioning
confidence: 99%
See 1 more Smart Citation
“…Flow measuring umes (hereinafter referred to as umes) with central contraction have been introduced as a cost-effective and simple approach for measuring water in rectangular open ditches and channels as it does not require complex in ow and out ow transition (Samani 2017; Kolavani et al 2018; Ghare et al 2020). The process produces critical ow in the contracted section resulting in a short-throated ume with no need for extended in ow and out ow transition (Samani 2017; Heyrani et al 2022). The contraction in rectangular umes is achieved by placing half cylinders in a perpendicular position inside the channel (Samani 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a possible error of up to 60% in the accuracy of umes could occur if the submergence ratio exceeds its limit and ow transitions from free ow to submerged condition. (Willeitner et al 2012;Goel et al 2015;Heyrani et al 2022).…”
Section: Introductionmentioning
confidence: 99%